Halal Pharmaceuticals: Legal, Shari'ah Issues And Fatwa Of Drug, Gelatine And Alcohol - Mustafa 'Afifi Bin Ab. Halim; Mohd Mahyeddin Mohd Salleh; Mohd Izhar Ariff Mohd Kashim; Azlin Alisa Ahmad; Norhaslinda Nordin (AESS Publications, 2024)
Indexed by ERA